Synthesis, Characterization and antioxidant activity study of Pyridine derivatives: A Comprehensive Study - Aijad Khan (Mathematical Statistician and Engineering Applications, 2023)
A preliminary investigation was conducted on 2-amino-4-aryl-3,5-dicarbonitrile-6-thiopyridines as a novel candidate as antioxidant research. A particular shape of the chosen pyridine derivatives having higher biological activity was taken with particular attention. Various structures were employed here. Yields for the target molecules under study ranged from 53% to 91%. The work that was presented demonstrated that the structure of the pyridine compounds under study affects their antioxidant activity.